2019
DOI: 10.7717/peerj.6124
|View full text |Cite
|
Sign up to set email alerts
|

Identification, expression, and phylogenetic analyses of terpenoid biosynthesis-related genes in secondary xylem of loblolly pine (Pinus taeda L.) based on transcriptome analyses

Abstract: Loblolly pine (Pinus taeda L.) is one of the most important species for oleoresin (a mixture of terpenoids) in South China. The high oleoresin content of loblolly pine is associated with resistance to bark beetles and other economic benefits. In this study, we conducted transcriptome analyses of loblolly pine secondary xylem to gain insight into the genes involved in terpenoid biosynthesis. A total of 372 unigenes were identified as being critical for oleoresin production, including genes for ATP-binding casse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 67 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…Resin from Boswellia has been viewed as one of the significant defense responses to wounding and pathogenic attacks ( Cabrita, 2018 ; Trapp and Croteau, 2001 ). Resin, synthesized via methylerythritol 4-phosphate (MEP) or mevalonic acid (MVA) pathways ( Bai et al., 2019 ; Mao et al., 2019 ), is transported to wounded sites through resin canals ( Khan et al., 2018b ; Mengistu et al., 2013 ). The resin is composed of more than 300 chemical constituents ( Al-Harrasi et al., 2019a ) identified as monoterpenes (KEGG pathway: map00902) and diterpenes (KEGG pathway: map00904), and triterpenes (KEGG pathway: map00909; map01062).…”
Section: Resultsmentioning
confidence: 99%
“…Resin from Boswellia has been viewed as one of the significant defense responses to wounding and pathogenic attacks ( Cabrita, 2018 ; Trapp and Croteau, 2001 ). Resin, synthesized via methylerythritol 4-phosphate (MEP) or mevalonic acid (MVA) pathways ( Bai et al., 2019 ; Mao et al., 2019 ), is transported to wounded sites through resin canals ( Khan et al., 2018b ; Mengistu et al., 2013 ). The resin is composed of more than 300 chemical constituents ( Al-Harrasi et al., 2019a ) identified as monoterpenes (KEGG pathway: map00902) and diterpenes (KEGG pathway: map00904), and triterpenes (KEGG pathway: map00909; map01062).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that some members of the AP2 family are involved in the biosynthesis of various secondary metabolites including terpenoids (Udomsom et al, 2016;Paul et al, 2017;Zhang et al, 2019). ABC transporters are involved in the transportation of secondary metabolites in plants (Yazaki, 2006;Crouzet et al, 2013;Fu et al, 2017;Mao et al, 2019). It has been reported that ABC transporter is one of the important differentially expressed genes in P. massoniana (Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Data available in the SRA database from three independent experiments were employed in this research [20][21][22] To detect correspondence of the transcripts to the genomic regions containing probes, all the assembled transcripts were aligned to the corresponding scaffolds with the BLASTn v.2.11.0 tool 59 , considering only alignments with a minimum e-value of 1e-30 and a transcript coverage of at least 75%.…”
Section: Rna-seq Data Analysismentioning
confidence: 99%
“…LP has a complex, poorly characterized and extremely large genome (1C=21.6 Gb) 17,18 , which until now could be assembled into only a highly fragmented draft reference genome with more than one million scaffolds and up to an 82% content of various highly repetitive DNA elements 19 . Due to such complexity, most LP genomic studies have focused on the analysis of nuclear gene sequences, which are important for the application of genomic data to the improvement of this conifer [20][21][22][23] , even in cases of limited information 24 .…”
Section: Introductionmentioning
confidence: 99%